Predictive modeling applications in actuarial science. Volume 2, Case studies in insurance - Frees, Edward W.; Meyers, Glenn; Derrig, Richard A. (New York : Cambridge University Press, 2016)
Predictive modeling uses data to forecast future events. It exploits relationships between explanatory variables and the predicted variables from past occurrences to predict future outcomes. Forecasting financial events is a core skill that actuaries routinely apply in insurance and other risk-management applications. Predictive Modeling Applications in Actuarial Science emphasizes life-long learning by developing tools in an insurance context, providing the relevant actuarial applications, and introducing advanced statistical techniques that can be used to gain a competitive advantage in situations with complex data. Volume 2 examines applications of predictive modeling. Where Volume 1 developed the foundations of predictive modeling, Volume 2 explores practical uses for techniques, focusing on property and casualty insurance. Readers are exposed to a variety of techniques in concrete, real-life contexts that demonstrate their value and the overall value of predictive modeling, for seasoned practicing analysts as well as those just starting out.
Title from publisher's bibliographic system (viewed on 08 Aug 2016).
Keywords: Actuarial science; Insurance -- Mathematical models; Forecasting -- Mathematical models